Electronic health record : a systems analysis of the medications domain - Scarlat, Alexander. (Taylor & Francis, 2012)
"This book introduces readers to structured systems analysis and the medications domains. It starts off with top-down decomposition of workflows and data. It applies structured systems analysis methodology and tools to electronic prescription, computerized physician order entry, drug dispensation, medication administration, and clinical decision support. Providing a comprehensive view of the EHR/EMR, the text covers user interface considerations, reporting requirements, and standards and vocabularies for meaningful use. Assuming no previous clinical and/or informatics knowledge, the author uses accessible language and includes over 250 figures and 100 review questions with answers"--Provided by publisher.